Teacher training in history subjects for the pupils with mild mental disabilities (psychological background) - Veselei, Michal (Civilia, 2019)
The work is focused in psychological aspects of teacher training for history teaching, where also pupils with mental disabilities are attended the class. It considers the starting approaches of the theories of goals and constructivicism developed by Jaean Piaget and Lev Vygotskij. Individual parts of the training preparation and class study contents are listed and characterized further.
Keywords: History; Constructivism; Mild mental disability; Preparation for teaching; Educational goasl; Elementary school